2017
DOI: 10.1093/ofid/ofx055
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Spontaneous Interferon-γ Secretion in Human Immunodeficiency Virus-Infected Persons

Abstract: Immune activation in human immunodeficiency virus (HIV) is a well described phenomenon. We found that HIV patients have higher secretion of interferon (IFN)-γ compared with non-HIV subjects, as measured by the “nil” value in the QuantiFERON-TB Gold test, even when viral loads are low. This may reflect ongoing immune activation, even with optimal HIV management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
(14 reference statements)
1
7
1
Order By: Relevance
“…These results are consistent with our previous report of elevated IFN-γ levels in a U.S. population with LTBI [ 15 ]. Our results are also consistent with a recent study conducted in Seattle, Washington that found higher geometric mean of QFT nil-tube IFN-γ values in QFT positive vs. QFT negative individuals with and without HIV infection, although these differences were not adjusted by comorbidities [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results are consistent with our previous report of elevated IFN-γ levels in a U.S. population with LTBI [ 15 ]. Our results are also consistent with a recent study conducted in Seattle, Washington that found higher geometric mean of QFT nil-tube IFN-γ values in QFT positive vs. QFT negative individuals with and without HIV infection, although these differences were not adjusted by comorbidities [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, in a sensitivity analysis that excluded participants with AMI, the association between IFN-γ and LTBI remained present. Unstimulated IFN-γ levels seemed overall higher than levels reported in prior studies [ 15 , 22 ], likely because our population was older, primarily inpatient, comorbidities were frequent, and socioeconomic conditions were different across studies. Therefore, these results should not be generalized to the overall population.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…IFN-γ is a cytokine secreted by activated T cells and NK cells with a wide range of immune response functions, such as macrophage activation, antiviral and antibacterial immunity mediation, and several other important immunoregulatory functions [44]. IFN-γ has been observed in higher concentrations within PWH compared to HD [45], and PWH with high levels of circulating IFN-γ exhibited a lower CD4 + T cell count recovery after 4 years of being on cART [46]. Additionally, IFN-γ trended positively with age among HD.…”
Section: Discussionmentioning
confidence: 99%